RELIGION AND ENVIRONMENTAL RESTORATION: An Interfaith Perspective to Address the Ecological Crisis - Endang Supriadi (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2026)
The growing global ecological crisis requires a multidisciplinary approach, including contributions from spiritual and religious dimensions. This study is important because it highlights the potential of world religions, through interfaith dialog and cooperation, in shaping environmental ethics and encouraging restorative action against natural destruction. This study aims to explore how an interfaith perspective can strengthen the contribution of religious communities in environmental restoration efforts, what forms interfaith collaboration can take in an ecological context, and how religious values from various traditions can converge to form an inclusive environmental ethic. Using qualitative methods based on literature study and discourse analysis, this research examines theological narratives and environmental praxis in religious documents, as well as interfaith initiatives that have been implemented in various local and global contexts. The main results show that there are universal values such as responsibility for creation, ecological justice, and simplicity of life that serve as common ground between religions in responding to the environmental crisis. In addition, faith-based collaborative practices are proven to strengthen the capacity of communities to manage and restore local ecosystems. The integration of religious perspectives in the environmental restoration movement not only enriches the ecological approach, but also broadens the base of public participation through a deep spiritual foundation.